Comparative Platelet Releasate Proteomic Profiling of Acute Coronary Syndrome versus Stable Coronary Artery Disease - Maguire, Patricia B.; Parsons, Martin E.; Szklanna, Paulina B.; Zdanyte, Monika; Münzer, Patrick; Chatterjee, Madhumita; Wynne, Kieran; Rath, Dominik; Comer, Shane P.; Hayden, Melanie; Ní Áinle, Fionnuala; Gawaz, Meinrad (Frontiers in Cardiovascular Medicine, 2020)
Upon activation, platelets release a host of soluble and vesicular signals, collectively termed the ‘platelet releasate’ (PR). The contents of this PR play a significant role in haemostasis, inflammation, and pathologic sequelae. Despite this, proteomic studies investigating the PR in coronary artery disease have not been performed. Here, we undertook a comparative label-free quantitative (LFQ) proteomic profiling of the 1U/ml thrombin-induced PR from 13 acute coronary syndrome versus 14 stable angina pectoris patients using a tandem mass spectrometry approach. Data are available via ProteomeXchange with identifier PXD009356. 318 PR proteins were identified across both cohorts with 9 proteins found to be differentially released, including tetranectin (CLEC3B), protein disulfide-isomerase-A3 (PDIA3), coagulation factor V (F5) and fibronectin (FN1). Strikingly, these 9 differential proteins were all associated with the gene ontology cellular component term ‘extracellular vesicle’ and reduced levels of EVs were detected in the corresponding plasma of ST-segment elevation myocardial infarction (STEMI) patients. Network analysis revealed 3 proteins either reduced (F5; FN1) or absent (CLEC3B) in the PR of STEMI patients that are strongly connected to both the clotting cascade and major druggable targets on platelets. This moderated proteomic signature may prove useful for non-invasive risk assessment of the progression of coronary artery disease. These data further contribute to the growing evidence-base of using the platelet releasate as a predictor of pathological state and disease severity.